Study on the Shear Failure of Reinforced Concrete Beams Using Extended Finite Element Method (XFEM) - Lateef, Hanadi Abdulridha; Laftah, Rafil Mahmood; Jasim, Nabeel Abdulrazzaq (Basrah Journal for Engineering Sciences, 2021)
This research concerns with the fracture behavior of reinforced concrete beams without shear reinforcement numerically. The software ABAQUS is adapted to simulate the crack propagation using the eXtended Finite Element Method (XFEM), taking into account materials nonlinearities using concrete damage plasticity CDP criteria. XFEM is used to solve the discontinuity problems in the simulation. The maximum principal stress failure criterion is selected for damage initiation, and an energy-based damage evolution law based on a model- independent fracture criterion is selected for damage propagation. The traditional nonlinear finite element analysis is used to specify the crack initiation position, which is required to specify the crack location in the analysis of beams using XFEM. Three-dimensional reinforced concrete beam models are investigated subjected to three and four-point loading tests. Simply supported beams under the effect of applied static load are investigated. An elastic perfectly plastic model is used for modeling the longitudinal steel bars. The main variables considered in the study are beam depth and the shear span with beam length. The numerical results are compared with the available experimental results to demonstrate the applicability of the model. The XFEM provides the capability to predict the concrete member fracture behavior.